Practice-Based Evidence to Support Return to Work in Cancer Patients - Désiron, Huget; Simons, Berthold; Spooren, Annemie; Camut, Stéphane; Van de Velde, Dominique; Otte, Thomas; Brunois, Théo; Van Kelst, Kirsten; Godderis, Lode (Frontiers in Rehabilitation Sciences, 2022)
Background: A large body of knowledge in international research emphasises on the importance of providing early, hospital based support in return to work (RTW) for cancer patients. Even though oncology health professionals are aware of the scientific evidence, current care practice does not show proof of implementation of this knowledge. Nevertheless, in care practice, health care professionals are building experience on this subject. This study – funded by the Belgian National Institute for Health and Disability Insurance - focuses on the evidence that is available based on these healthcare professionals’ experiences in care-practice. Methods Using qualitative research methods, and based on preliminary literature research, semi-structured interviews with oncology health care professionals was used as orienting information. Results of the analyses of these interviews lead to the guideline for focusgroup discussions with managers in oncology hospitals. Results: Of all hospitals in Belgium that provide oncology health services, 75% participated in this research, some of them as well in part 1 (interviews) as in part 2 (focusgroup discussion). Five themes that influence care providers and staff to implement scientific evidence on RTW in cancer patients were detected: 1) Opinions on the role that care-institutions can take in RTW-support ; 2) Current content of RTW-support during onco-care; 3) Scientific bases; 4) Barriers and success factors (“mirror-effect”); 5) Legal rules & (private insurance) regulations. What heath care providers see as best practice / ideal scenario was clarified. Conclusions: The final report of this study clarifies that in practice evidence is available that integrates that is included in “current care” in very different ways. Care providers work on setting up a process to do so, that starts with indication setting) and ends with a fixed endpoint that is clearly agreed upon by health care professionals & patients. To inspire the NIHDI, points of interest to be included in regulation are identified, both on patient level and on hospital level.